2000
DOI: 10.1017/s0376892900000205
|View full text |Cite
|
Sign up to set email alerts
|

Trophic cascades in benthic marine ecosystems: lessons for fisheries and protected-area management

Abstract: An important principle of environmental science is that changes in single components of systems are likely to have consequences elsewhere in the same systems. In the sea, food web data are one of the few foundations for predicting such indirect effects, whether of fishery exploitation or following recovery in marine protected areas (MPAs). We review the available literature on one type of indirect interaction in benthic marine ecosystems, namely trophic cascades, which involve three or more trophic levels conn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
369
2
13

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 446 publications
(391 citation statements)
references
References 167 publications
(241 reference statements)
7
369
2
13
Order By: Relevance
“…Restructuring of fish communities has been revealed by the reintroduction of top predatory species in a variety of marine systems (Pace et al 1999, Pinnegar et al 2000. Here we observed evidence for community restructuring based on both body size and trophic score.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…Restructuring of fish communities has been revealed by the reintroduction of top predatory species in a variety of marine systems (Pace et al 1999, Pinnegar et al 2000. Here we observed evidence for community restructuring based on both body size and trophic score.…”
Section: Discussionmentioning
confidence: 51%
“…Trophic cascades have been observed in a variety of marine communities (Steneck 1998, Daskalov 2002, Graham et al 2003, Frank et al 2005, Mumby et al 2006, though the most distinct examples come from relatively simple systems with few trophic levels and low species diversity (Strong 1992, Pinnegar et al 2000. Indeed, the buffering effects of varied and differentiated consumptive relationships, including omnivory and ontogenetic trophic level shifts, as well as multiple prey refuges, may prevent strong trophic cascades in more speciose systems (Strong 1992).…”
Section: Introductionmentioning
confidence: 99%
“…The pattern of response (i.e., reserve effects) of top-trophic level species is expected to correlate positively with the age, size, and enforcement capacity of the reserves under consideration Russ 2006;Guidetti et al 2008;Claudet et al 2008). On the contrary, nonexploited prey species in the reserves are expected to have minimal response or even respond negatively due to concomitant increase in predation pressure (Pinnegar et al 2002;Graham et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…It has been previously suggested that populations of giant kelp and sea urchins are coupled in nature (Mann and Breen 1971, Dayton et al 1992, Pinnegar et al 2000, and purple sea urchins are thought to be very closely connected to the habitat of algal populations for their primary food source Reed 1985, Pearse 2006). In the Baja California region, the purple sea urchin is often associated with giant kelp forests (Palleiro-Nayar et al 2008, Salgado-Rogel et al 2006.…”
Section: Discussionmentioning
confidence: 99%
“…Authors have previously suggested that populations of giant kelp and sea urchins are coupled in nature (Breen and Mann 1976, Dayton et al 1992, Pinnegar et al 2000, showing similar responses to environmental changes, as urchins are closely tied to algal habitat for their primary food source (Harrold and Reed 1985, Graham 2004, Pearse 2006. However, most of this work has been performed in northern temperate populations for sea urchins and for the giant kelp, Macrocystis pyrifera, whereas the kelp forest populations in Baja California Sur are known to respond to and recover from warming events such as El Niño in a different manner (Ladah et al 1999, Edwards 2004, Ebert 2010.…”
Section: Introductionmentioning
confidence: 99%